The effect of unrefined sugar on inflammation: a systematic review of intervention studies - Ebadi, Samarghand; Azlan, Azrina (Medknow Publications, 2023)
Background: It is well established that unrefined sugarcane products have antioxidant activity due to phytochemicals, polyphenols, and total antioxidant capacity, which may decrease inflammation and oxidative stress. Therefore, we conducted a systematic review to evaluate the association of unrefined sugar consumption with inflammatory biomarkers. Methods: Google Scholar, ScienceDirect, Scopus, Cochrane Library, and ProQuest databases were searched up to December 2021 for studies that report the effect of unrefined sugar on inflammation according to inflammatory cytokines, chemokine, and adhesion molecules as outcome measures. Results: Thirty‑six studies were evaluated. Across all research, five studies (two in vitro and three animal studies) reported the effect of unrefined sugar on levels of cytokines, including IL‑6, TNF‑α, IL‑10, IL‑1β, and IFN‑γ. Additionally, the quality of the studies was assessed for risk of bias. Conclusions: it is possible to affirm that unrefined sugarcane products, including jaggery, may have a protective effect on inflammation via regulating some of the inflammatory pathways and a favorable impact on cytokines secretion according to the results of in vitro and animal model studies. However, since the findings are still insufficient, more scientific research, especially well‑designed human trials, is highly recommended to conclude the outcomes confidently. Human data may encourage industries and the public to replace purified sugar with unrefined sugarcane in sugar‑based food and for further health‑care policy decisions.